Qur’anic Persfective on Science : Implications for Islamic Education Curriculum - Kurniawan Dwi Antoro; Rahmawati Eka Nurhidayah; M. Makhrus Ali (JISEI: Journal of Islamic Studies and Educational Innovation, 2025)
The holy book of the Qur'an as the main source of Islamic teachings contains many verses related to science and knowledge. The perspective of the Qur'an on science does not only emphasize the empirical aspect, but also the integration of divine values ​​in the pursuit of knowledge. This article aims to explore the relationship between the Qur'an and science and its implications in the development of Islamic education curriculum. Using a qualitative approach based on literature studies, this article analyzes the verses of the Qur'an related to science and how these concepts can be implemented in Islamic education. The results of the study show that the integration of science and Islamic values ​​in the education curriculum can form a holistic paradigm that includes aspects of rationality, ethics, and spirituality. Thus, the Islamic education curriculum needs to accommodate an integrative approach that connects modern science with Islamic values ​​in order to produce a generation that is faithful, knowledgeable and has noble character.